Pengaruh Entrepreneurship Education, Entrepreneurial Traits Dan Digital Litercay Terhadap Readiness Of Entrepreneurship (Studi Kasus Pada Mahasiswa Universitas Islam Malang Angkatan 2020) - Cahyani, Amelia Dwi; Susyanti, Jeni; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to find out how much influence entrepreneurship education, entrepreneurial traits, and digital literacy have on readiness for entrepreneurship. This type of research is explanatory research with a quantitative approach. The population that is the focus is the students of the Islamic University of Malang class of 2020. A total of 96 students were selected as samples using a purposive sampling technique. Data collection was carried out through a questionnaire distributed via Google Form and the results were analyzed using multiple linear regression using Statistical Program Social Science (SPSS) version 26. The results of the research showed that entrepreneurship education had an effect on readiness of entrepreneurship, entrepreneurial traits had an effect on readiness of entrepreneurship and digital literacy also influences readiness of entrepreneurship. Keywords: Entrepreneurship Education, Entrepreneurial Traits, Digital Literacy, And Readiness Of Entrepreneurship.